EFFECT OF LIVE STREAMING E-COMMERCE IN BUILDING CUSTOMER TRUST AND CUSTOMER ENGAGEMENT (STUDY ON TOKOPEDIA CONSUMERS) - Jodhi Kartha Yudha; Rita Komaladewi; R. Thomas Budhyawan Yudha (JOURNAL OF BUSINESS STUDIES AND MANGEMENT REVIEW, 2022)
In recent years, e-commerce in Indonesia is growing rapidly which makes the level of competition between e-commerce is also high and has resulted in the closure of several e-commerce because they are unable to compete. It can be said that live streaming is one of the innovations as a marketing strategy for new e-commerce. To avoid suspicions of different product characteristics photos, fake shops, fraudulent sellers and others and to increase customer trust, Tokopedia Play created a live shopping experience feature. And can increase customer engagement which ultimately consumers buy and revisit. This study aims to examine the effect of live streaming, customer trust, and customer engagement in making online purchases on Tokopedia e-commerce. The independent variable in this study is live streaming. The dependent variable is customer engagement. And the intervening variable is customer trust. Respondents in this study were people who had shopped online through live streaming on Tokopedia Play. This study uses quantitative research methods and PLS analysis. Using a minimum of 105 respondents. The results of the study show that: (1) Live streaming has a positive and significant effect on customer trust. (2) Customer trust has a positive and significant effect on customer engagement. (3) The effect of live streaming on customer trust and on customer engagement is significant and positive.